Analisis Manajemen Rantai Pasok (SCM) UMKM Gethuk Lindri di Desa Kertosari - Rifqi Wahyu Ichwannudin; Rizky Alifian Nugroho; Muhammad Azib Hafizuddin; Aloysius Tommy Hendrawan (Jurnal Kendali Teknik dan Sains, 2025)
The supply chain is a network of companies that work together to produce and deliver products to end users. UMKM Getuk Lindri Bu Umi has problems related to the management of cassava raw material inventory used in Getuk Lindri production, namely the supply of raw materials, storage of raw materials, and product marketing. The purpose of this study is to analyze the supply chain management (SCM) used by MSMEs in carrying out their production processes to be effective and efficient in achieving predetermined goals. The method used in this research is a qualitative method carried out as much as observation and direct observation of MSME owners. The solutions offered include establishing communication with suppliers or adding new suppliers who are more cooperative, collaborating with universities to get better storage technology.